Design of Smart Farm Irrigation Monitoring System Using IoT and LoRA - Kurniawan D. Irianto (Ikatan Ahli Informatika Indonesia (IAII), 2022)
Agriculture is an essential part of society in Indonesia because most of the population lives off of farming. Water and irrigation are the most critical and central factors in the agricultural system. The uneven distribution of irrigation water can be a problem for farmers. In addition, most of the current irrigation systems are still operated manually, for example, irrigation gates. The gate still works manually and requires human labor to run it. This study aims to design a smart farm irrigation system using internet of things and LoRa communication technology. LoRa can transmit information up to a range of several kilometers without an internet connection. It will be advantageous when the farm's location is deep in the forest, and there is no GSM signal for internet access. This study indicates that this system brings benefits for farmers in running agriculture. Farmers' work time is shorter. They can use the remaining time to do other businesses to increase their income. The irrigation monitoring process becomes easier because they do not need to come to the farm location. In fact, they can use smartphones to monitor it.